Epidoxorubicin versus no treatment as consolidation therapy in advanced ovarian cancer: results from a phase II study. (1st January 2006) - Bolis, G.; Danese, S.; Tateo, S.; Rabaiotti, E.; D'Agostino, G.; Merisio, C.; Scarfone, G.; Polverino, G.; Parazzini, F.
Abstract : To compare the effect of epidoxorubicin given for 4 months versus no treatment in the survival of patients with advanced ovarian cancer and complete pathologic response after first-line surgery and chemotherapy with platinum-based schedules, we conducted a multicenter randomized clinical trial. Patients with histologic diagnosis of epithelial ovarian cancer FIGO stage III or IV at first diagnosis; complete pathologic response at second-look laparotomy/laparoscopy or complete clinic response; and those who have had first-line therapy including surgery and one regimen containing cisplatin or carboplatinum were eligible for the study and were randomly allocated to epidoxorubicin 120 mg/sqm or no treatment. A total of 64 women were allocated to epidoxorubicin and 74 to no treatment. There were 20 and 19 deaths, respectively, in the epidoxorubicin and no-treatment groups. The 3-year percent overall survival was 79.0% and 78.7%, respectively, in the no-treatment and epidoxorubicin groups (log-rank test, P = 0.93).